Optimalisasi Kesiapan Akademik dan Profesional Mahasiswa Baru D III Farmasi Melalui Program PKKMB Terintegrasi di Akademi Farmasi Dwi Farma Bukittinggi - Ramadhani, Indrie; Naim, ‘Ainun; Dinil Haq, Ahdi; Yonrizon, Yonrizon; Marjoni, Mhd Riza (Civiliza Publishing, 2024)
Introduction to New Student Campus Life (PKKMB) is a crucial component in preparing students to face academic and professional challenges. This activity outlines the implementation of an integrated PKKMB program at the Dwi Farma Pharmacy Academy in Bukittinggi for new students in the D-III Pharmacy program. The main innovation of this program lies in the combination of three key elements: comprehensive academic preparation, guest lectures from experienced pharmacy practitioners, and intensive personal development training.The implementation methods include curriculum orientation sessions, interactive discussions with industry experts, and soft skills workshops. Program evaluation is conducted through pre-tests and post-tests, as well as participant satisfaction surveys. Results show a significant improvement in students' understanding of the D-III Pharmacy curriculum structure, insights into various career prospects in the pharmaceutical field, and mastery of soft skills relevant to industry demands. This integrated PKKMB model proves effective in bridging the gap between academic expectations and professional realities. The success of this program can serve as a reference for other pharmaceutical vocational education institutions in designing orientation programs that are not only informative but also inspirational and industry-oriented. Recommendations for further development include involving alumni as mentors and closer collaboration with industry partners